Postojna-Planina Cave System in Slovenia, a Hotspot of Subterranean Biodiversity and a Cradle of Speleobiology - Maja Zagmajster; Slavko Polak; Cene Fišer (Diversity, 2021)
The Postojna-Planina Cave System (PPCS) in central Slovenia is a globally exceptional site of subterranean biodiversity, comprised of many interconnected caves with cumulative passage length exceeding 34 km. Two rivers sink into the caves of the PPCS, called the Pivka and Rak, and join underground into Unica River, which emerges to the surface. The studies of fauna of PPCS began in the 19th century with the first scientific descriptions of specialized cave animals in the world, making it “the cradle of speleobiology”. Currently, the species list of PPCS contains 116 troglobiotic animal species belonging to eight phyla, confirming its status as the richest in the world. Of these, 47 species have been scientifically described from the PPCS, and more than 10 await formal taxonomic descriptions. We expect that further sampling, detailed analyses of less studied taxa, and the use of molecular methods may reveal more species. To keep the cave animals’ checklist in PPCS up-to-date, we have supplemented the printed checklist with an online interface. As the revised checklist is a necessary first step for further activities, we discuss the importance of PPCS in terms of future research and conservation.